2017
DOI: 10.14453/aabfj.v11i1.6
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Firm Performance: Evidence from Saudi Arabia

Abstract: This study aimed to measure the impact of Corporate Governance on Firm performance of listed companies in Saudi stock exchange. The study methodology was a pooled data collected from the Saudi stock exchange (TADAUWL) for the period from 2012 to 2014. The study sample is 171 listed companies. The study independent variable is Corporate Governance principals. The dependent variable is Firm performance which was measured using ROA, ROE and Tobin's Q. The study also utilized five control variables in order to hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
168
4
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(206 citation statements)
references
References 21 publications
20
168
4
14
Order By: Relevance
“…It means that institutional ownership does not have influence on financial distress, similar to managerial ownership and audit opinion which have insignificant result on financial distress. The result is not consistent with the research of Suntaruk (2009), Li et al (2008), Sheikh et al (2013), Manzaneque et al (2016), and Buallay et al (2017).…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…It means that institutional ownership does not have influence on financial distress, similar to managerial ownership and audit opinion which have insignificant result on financial distress. The result is not consistent with the research of Suntaruk (2009), Li et al (2008), Sheikh et al (2013), Manzaneque et al (2016), and Buallay et al (2017).…”
Section: Resultscontrasting
confidence: 78%
“…Li et al (2008) and Miglani et al (2014) found a positive relation between audit opinion and financial distress. Buallay et al (2017) also found that audit quality has a significant positive influence on the company's performance.…”
Section: Introductionmentioning
confidence: 87%
“…Based on the value of path coefficient, the results also prove empirically that the better implementation of GCG will improve company performance. The study results are supported by very many previous research results which generally stated that the implementation of GCG can improve the company performance, such as Andriana & Panggabean find that GCG mechanism simultaneously have significant effect on financial performance [13], Tornyeva & Theophilus show that GCG has positively associated with the financial performance [17], Fidanoski et al also show that GCG mechanism has positively related to the bank's profitability measures by ROA [18], and Mustapa, Rizad & Ghazali argue that GCG has related to firm performance [5], and Buallay et al show that GCG has positive impact on firm performance, and others [26]. Based on the results of interviews with the management of sharia banking, the implementation of GCG in terms of principles will be able to encourage the realization of good company performance as well.…”
Section: B the Influence Of The Implementation Of Good Corporatementioning
confidence: 99%
“…Corporate governance is crucial in building investors' trust and attracting investors to the marketplace (Buallay et al, 2017). The impact of corporate governance on firm performance is therefore of great importance to shareholders.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%